Cancer‐associated adipocytes promote pancreatic cancer progression through SAA1 expression. Issue 8 (6th July 2020) - Takehara, Masanori; Sato, Yasushi; Kimura, Tetsuo; Noda, Kazuyoshi; Miyamoto, Hiroshi; Fujino, Yasuteru; Miyoshi, Jinsei; Nakamura, Fumika; Wada, Hironori; Bando, Yoshimi; Ikemoto, Tetsuya; Shimada, Mitsuo; et al.
Abstract: Although pancreatic cancer often invades peripancreatic adipose tissue, little information is known about cancer‐adipocyte interaction. We first investigated the ability of adipocytes to de‐differentiate to cancer‐associated adipocytes (CAAs) by co‐culturing with pancreatic cancer cells. We then examined the effects of CAA‐conditioned medium (CAA‐CM) on the malignant characteristics of cancer cells, the mechanism underlying those effects, and their clinical relevance in pancreatic cancer. When 3T3‐L1 adipocytes were co‐cultured with pancreatic cancer cells (PANC‐1) using the Transwell system, adipocytes lost their lipid droplets and changed morphologically to fibroblast‐like cells (CAA). Adipocyte‐specific marker mRNA levels significantly decreased but those of fibroblast‐specific markers appeared, characteristic findings of CAA, as revealed by real‐time PCR. When PANC‐1 cells were cultured with CAA‐CM, significantly higher migration/invasion capability, chemoresistance, and epithelial‐mesenchymal transition (EMT) properties were observed compared with control cells. To investigate the mechanism underlying these effects, we performed microarray analysis of PANC‐1 cells cultured with CAA‐CM and found a 78.5‐fold higher expression of SAA1 compared with control cells. When the SAA1 gene in PANC‐1 cells was knocked down with SAA1 siRNA, migration/invasion capability, chemoresistance, and EMT properties were significantly attenuated compared with control cells. Immunohistochemical analysis on human pancreatic cancer tissues revealed positive SAA1 expression in 46/61 (75.4%). Overall survival in the SAA1‐positive group was significantly shorter than in the SAA1‐negative group ( P = .013). In conclusion, we demonstrated that pancreatic cancer cells induced de‐differentiation in adipocytes toward CAA, and that CAA promoted malignant characteristics of pancreatic cancer via SAA1 expression, suggesting that SAA1 is a novel therapeutic target in pancreatic cancer. Abstract : Cancer‐associated adipocyte (CAA) promotes migration/invasion of pancreatic cancer cells. CAA also induced pancreatic cancer cells drug resistance, epithelial‐mesenchymal transition.